DNA profiling of bacteria from human hair: Potential and pitfalls - Tridico, S.; Murray, D.; Bunce, Michael; Kirkbride, K. (John Wiley & Sons Ltd, 2017)
© 2017 John Wiley & Sons Ltd. All rights reserved. Human hair is one of the most ubiquitous types of biological trace evidence encountered in forensic investigations. However, despite their prevalence, there is a paucity of research regarding the usage of metagenomic analysis applied to human hair as a tool in the forensic molecular toolkit. Recent studies have provided a glimpse into the forensic potential of metagenomic analyses of bacteria present on scalp and pubic hairs as a means of demonstrating contact between individuals. The most promising avenue for bacterial DNA profiling appears to lie with niche-specific bacteria that colonize hair from the female urinogenital area. However, the evaluation of metagenomic analyses of human hair in forensic investigations is still in its infancy, the true potential of this novel technique can only be realized by further, more targeted and nuanced research.